Netolerantnost v Sloveniji in Evropi - Kirbiš, Andrej (Družboslovne razprave, 2012)
Our study draws on postmodernisation theory to examine and compare the social intolerance of Slovenians and Europeans toward nine minority groups. We analysed 44 representative national samples in European Values Study (2008) and Slovenian Public Opinion data. In 2008 Slovenians were most intolerant of drug addicts, heavy drinkers and the Roma, who remain the least desired ethno-religious group in Slovenia and Europe. A multilevel regression model showed that at the cross- -country level higher intolerance was only predictedby lower levels of socioeconomic development and not by other macro variables. Significant predictors at the individual level proved to be education, household income, age and religiosity. In Slovenia during the 1992-2008 period levels of intolerance toward lifestyle minorities remained ata similar level, while xenophobia decreased.
Keywords: Social marginality; Družbena obrobnost; Marginal groups; Marginalne skupine; Toleranca; Tolerance; Xenophobia; Ksenofobija; Slovenia; Slovenija; Europe; Evropa